Pengaruh Model Pembelajaran TPS terhadap Hasil Belajar Kognitif Biologi Siswa Putra Kelas XI SMAN di Banjarmasin - Siti Ramdiah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Teachers need to know deeper about learning style and how to facilitate students’ needs in learning in order to stimulate students’ thinking skill which might affect students’ cognitive learning outcome. Teachers can facilitate students’ learning style and needs by designing teaching instruments which develop students’ thinking skill. This current study focused on male students whose learning outcome was considered low compared to female students based on previous studies. Because of this male students’ characteristic, this study employed TPS learning model which is believed be able to facilitate the students’ characteristics and learning style. The purpose of this study was to analyze the effect of Think, Pair, and Share (TPS) learning model to cognitive learning outcome of Biology toward the XI grade of male high school students majoring natural science (IPA). The participants of this study consisted of 22 male students from IPA on the state high schools in Banjarmasin. This study employed quasi-experimental design by using “nonequivalent pretest-post test control group design” model. Regarding limited number of the male students in the natural science classes, this study involved four classes. The control class was from XI IPA 2 of SMAN 10 and XI IPA 4 SMAN 13 Banjarmasin with totally 11 students. Meanwhile, the experimental class was from XI IPA 3 of SMAN 12 and XI IPA 3 SMAN 13 with 11 students as well. The data were obtained by using an essay test and the scoring rubric which was referred to Hart with interval 0–4. Then, they were analyzed using one way Anova through SPSS 17.0 for Windows. The homogeneity and the normality tests were done as the pre-requirement. The result of this study showed that TPS learning model affected the male students’ learning outcome. The finding revealed that TPS is potential for improving male students’ learning outcome. The data also support the findings of previous studies related to male students’ academic achievement.Keywords:        TPS, Cognitive learning outcome, Male students